PC Remote Control - Ibraheem Azzam AL-Adham; Adham Noman Dwikat (My University, 2009)
In Our Hardware Graduation project we made a PC Remote Control that used to control the computer as any electric device existing at home using a remote control device.The aim of this project is to create MicroConroller that control the computer like any device in the home using any remote control, i.e. we didnt make our remote control you can use any remote exists .The programs needed to run the program is our program we made needs only .Net Framework redistributable

: (IR Remote Control)      (mouse)                   (motherboard)
PC Remote Control